Occupy in Deutschland : die Protestbewegung und ihre Akteure - Geiges, Lars, 1981- (Studien des Göttinger Instituts für Demokratieforschung, 2014)
Suddenly, they were there with their tents: In 2011, the Occupy movement seemed to form overnight, occupying public spaces all over the world and protesting against the power of banks. Occupy-groups also formed in Germany, sometimes setting up camps that went on for months in urban centers. From here, their protest would unfold - open, democratic, polyphonic. What moved the activists, and how did they view politics, the state, and society? How did they organize? And what might remain of Occupy? Through observations, interviews, and discussions with Occupiers, Lars Geiges opens up a well-endowed view of the recent and scarcely explored protest phenomenon.